Perbedaan Cara Pembukusan, Waktu Penyajian, dan Kombinasi Cara Pembukusan dan Waktu Penyajian Memberikan Efek Konsentrasi Timbal Pada Makanan Jajanan - Praditasari, Afiana; Sunarto, Sunarto (JURNAL RISET GIZI, 2013)
Background : Lead in the atmosphere can contaminate foods that is sold near the street. Lead and its organic compounds can be hazardous to health and causes various negative effects biologically. When accumulation of lead occurs in our body, it can cause disorders in hematopoietic system, nervous system, reproduction system, the function of kidney, and has an effect on the development of the brain on under-five-years-old children.Objektive : The purpose of this study is to find out the difference of wrapping, time of serving, and combination beetwen wrapping and time of serving have effect on lead concentration in street foodsMethod : This study is an analytic observational study with prospective cohort approach, this study was performed on street foods that were sold near the street in front of Java Supermall, Semarang. Total of samples were 36 samples from two types of foods, that was defined using purposive sampling method. Type of food, category of wrappings and time of serving were found out using observation and inspection, whereas the concentration of lead in food was measured using Atomic Absorption Spectrophotometer method.Results : The average concentration of lead was measured for each type of food, it was 4.85 ppm for kue lapis (multi-layered cake) and 5.39 ppm for gethuk lindri (noodle-like cassava cake). The average concentration of lead in food that was completely wrapped was 2.91 ppm, whereas for food that was only one-half wrapped was 8.01 ppm. The average concentration of lead at 0 hour (at 01.00 pm West Indonesia Time) was 2.79 ppm, 5.41 ppm at 2 hours (at 03.00 pm West Indonesia Time) and 7.10 ppm at 4 hours (at 05.00 pm West Indonesia Time).Conclution : The difference of wrappings, time of serving, and combination beetwen wrapping and time of serving have effect on lead concentration in street foods.